Inclusive security, lasting peace an interview with Ambassador Swanee Hunt. (Journal of International Affairs, 2013)
"As U.S. Ambassador to Austria from 1993-1997, Swanee Hunt played an important role in U.S. foreign policy toward the Balkans during the Bosnian War. During and after her tenure as ambassador, Hunt made multiple trips throughout Eastern Europe and became a specialist in the role of women in post-communist Europe. It was in the Balkans where she realized that women were absent from the negotiating table. As a result, Hunt founded the Washington, DC-based Institute for inclusive Security in 1999, which conducts research, training, and advocacy to integrate women into peace processes. In total, the organization has trained more than 2,000 women peacebuilders from countries in conflict, including Afghanistan, Iraq, Lebanon, Liberia, Congo, Sudan, Colombia, and Sri Lanka, among others. Ambassador Hunt spoke with the Journal about the unique contributions of women to peace."